Recombinant modified vaccinia virus Ankara-based malaria vaccines. (2nd January 2016) - Sebastian, Sarah; Gilbert, Sarah C.
Abstract : A safe and effective malaria vaccine is a crucial part of the roadmap to malaria elimination/eradication by the year 2050. Viral-vectored vaccines based on adenoviruses and modified vaccinia virus Ankara (MVA) expressing malaria immunogens are currently being used in heterologous prime-boost regimes in clinical trials for induction of strong antigen-specific T-cell responses and high-titer antibodies. Recombinant MVA is a safe and well-tolerated attenuated vector that has consistently shown significant boosting potential. Advances have been made in large-scale MVA manufacture as high-yield producer cell lines and high-throughput purification processes have recently been developed. This review describes the use of MVA as malaria vaccine vector in both preclinical and clinical studies in the past 5 years.